One-dimensional problems with free boundaries in ecology - Berezovs'kyi, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
Statements of problems with free boundaries are given for nonlinear parabolic equations arising in ecology and medicine. Some constructive methods for their solution are considered.